Очерки. Воспоминания - Федорченко-Шемякина Лидия Николаевна (Признание в любви родному городу, 1993)
Экземпляры: кр (20210329) / Инвентарный номер: 33027 / Авт.знак: Ф33 / ГРНТИ: 03.23 / ББК: 63.3(2Рос.Удм-2Сарапул)